FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAMPUAN MOTORIK ANAK USIA 12-18 BULAN DI KELUARGA MISKIN DAN TIDAK MISKIN - Vita Kartika; S. Latinulu (Persagi, 2002)
FACTORS INFLUENCED ON MOTORIC PERFORMANCE OF CHILDREN AGED 12-18 MONTHS OF POOR AND WELL OF FAMILIES.Background: The development of rough motoric is one process during early child growth is influenced by some factors such as nutritional status, energy and protein intake and activities.Objectives: To find out related and dominant factors as well as dominant factors which influenced rough motoric performance of children.Methods: Cross sectional study was conducted in Ciomas sub district, Bogor district. West Java. Samples are children aged 12-18 months and belongs to poor and well off families. There are 23 children of the poor and 20 children of the well off families were choosen purposively. Data were analised out using Chi square test and logistic regression test of the SPSS program.Results: There were significant differences between rough motoric performance of the children of the two groups (p<0.05). The were 20 children (46.5%) had slow rough motoric development; 15 (65.2 %) of them were derived poor families and 5 (25.0%) children from well off families, 6 out of 15 (40.0%) children from poor families had weight for height Z- score < -2 SD and 9 (60.0%) children had Z-score > -2 SD. Amount of energy and protein intake were significantly related to rough motoric development of the children (p<0.05). There are 10 out of 15 (66.7%) children of poor families who suffenng from slow rough motoric development also suffering from Jack of energy and 12 (80.0%) children lack of protein Intake. It was also found that rough motoric performance of children significantly related to their activities (p<0.05), namely 7 (46.7%) children found that decreased their activities. Determinant factors of rough motoric performance in early child development were suficient energy and protein intake showed by equation model: Y = 1.5134 + 1,2915* Energy + 1,3539* Protein.Conslusions: Significant factors that related to rough motoric performance of the children were energy and protein intake and their activities.Keywords: rough motoric performance, nutritional status, energy and protein intake, children activities